The anti-arthritic and anti-inflammatory activities of aqueous extract powder bark of Anthocleista schweinfurthii Gilg (Loganiaceae) - Djova, Valdi Steve; Nyegue, Ascension Maximilienne; Etoa, François-Xavier (Journal of Drug Delivery and Therapeutics, 2018)
Aqueous extract bark of Anthocleista schweinfurthii (ASE) was investigated for anti-arthritic, anti-inflammatory activities and phytochemicals screening. Phytochemical screening was carried out according, to LC-MS procedures, the anti-inflammatory effect of ASE was evaluated in vitro inhibition of 15-lipoxygenase (15-LOX) enzyme and  proteinase inhibiting action assays. The anti-arthritic activity was performed according to the Bovine Serum Albumin (BSA) test. The chemical composition of ASE showed that it was mainly composed of isocyanate, biphenyltriol, methoxyflavanone, soscoparin and glucopyroside. In the anti-inflammatory assays, ASE showed selective inhibition of 15-lipooxygenase with IC50 value of and moderate activity against the inhibition of proteinase action with IC50 value of L. Both the methods  showed that the ASE posses good anti-inflammatory activity. ASE had strong in vitro anti-arthritic activity with IC50 of , the positive control Diclofenac had IC50 value of  The result of this study justified the use of this plant in traditional Cameroonian medicine in the treatment of inflammation. ASE may offer a new source of potential therapeutic agents for the effective treatment of arthritis and inflammation.  Keywords: Anthocleista schweinfurthii, phytochemical screening, anti-arthritic activity, anti-inflammatory activity,